Farmers’ Risk Behavior in Organic and Inorganic Rice Farming - Sri Fajar Ayu; Patricia Srisere Ikaria Situmorang; Meutia Nauly; Iman Arman (Institut Pertanian Bogor, 2026)
The purpose of this study was to compare the productivity, income, and risk-taking behaviors of organic and non-organic rice farmers in Serdang Bedagai Regency, North Sumatra Province. The study took a descriptive-quantitative approach, surveying 62 rice producers (31 organic and 31 non-organic). The analysis included measures of productivity, income, production, and income risk, as well as a sensitivity analysis to analyze the impact of price and cost changes. The results demonstrate that organic rice productivity (1,924 kg/ha) was lower than non-organic rice (4,668 kg/ha); however, overall net income for organic farming (IDR 32.15 million/ha) was higher than non-organic farming (IDR 27.28 million/ha) due to more stable and higher rice prices. Production and income risks are better managed in organic farming, with lower variation coefficients than in non-organic systems. The sensitivity analysis shows that even with a 20% fall in selling price or a 20% rise in production expenses, organic rice cultivation still earns a profit. Most organic farmers are risk averse, whereas non-organic farmers are more willing to take risks. These data support the claim that organic rice cultivation is more economically viable and environmentally sustainable than conventional systems. Keywords: income, organic rice, risk behavior, sensitivity analysis, sustainability